THE SELF-CONCEPT IN THE PERSONAL COMPONENT OF INDIVIDUAL EXPERIENCE STRUCTURE - Севост`янов, Павло Олександрович (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
The article analyzes the relation of the self-concept with the personal component of the individual experience features. The contents of the self-concept, the feeling of well-being of my own self, and the personal component of individual experience are summarized briefl. The structural organization of individual experience and its dynamic aspect are considered. The use of the personal model of the Big Five as one of the theoretical foundations of the research is substantiated. Comparison of different elements of the personal component of individual experience is conducted from the point of view of their most representative representation of the personal component of individual experience. The theoretical substantiation of the research of the selfconcept in the structure of the personal component of the individual experience is carried out. A generalization of the results of previous studies has been done. An empirical study was conducted by the 154 students of the Slavic National University and the V.N. Karazin Kharkiv National University. In the course of the research, factorization of the indicators of the self-concept was carried out, which resulted in two factors which can be conventionally called the prosperous and problematic perception of self-concept. In the further cluster analysis, the four groups (profies) were obtained, each of one is representing a certain personality component of individual experience features - from a safe to a conflct. It is possible to provide further comparison the received profies as representational characteristics of the personal component of individual experience for a deeper understanding of the processes inherent in this component.